Imaginarios sociales y hábitos de alimentación influenciados por redes sociales en adolescentes de edades entre 14 y 16 años (2020)
Because of the outgrowing feeding and eating disorders statistic, as well diabetes, cardiovascular disease, and their association to secondary disorders as anxiety or depression; investigators around the world are interested on knowing the relation between mental health and eating behaviors; this investigation is taking from the actual context of technology and communication, and center on uses of social network and the continuous content related to eating, nutrition, diets, exercise routines, and the social life virtualization. This qualitative research objective was aimed to interpret how the social imaginary are built about eating behaviors influenced by social networks in a group of five teenagers between 14 and 16 year of Cartago- Valle. The theorical frame work is focused from categories eating and feeding disorders, eating behaviors, social media networks, mental health, social imaginary and teenagers. The research's methodology is framed on a semi-structured interview. On the research as an achievement to identify information about uses of social networks and how teenagers social imagenery has built eating habits, and the concept of needing avoiding/restrictive behaviors in order to have a healthy lifestyle as well the tendency of needing to be connected. In conclusion the needing of campaigns on promoting healthy eating behaviors and safe social media uses. And the relevance on preventing mental health disorders and social networks abuse.